Influence of early maternal separation on susceptibility to the activity-based anorexia model in male and female Sprague Dawley rats. (November 2022) - Morgan, Godstime Stephen Kojo; Mata, Yolanda; Urbano, Beatriz Carrillo; Suárez de Puga, Ricardo Pellón; Guirao, Paloma Collado; Gotti, Stefano; Sànchez, Helena Pinos
Abstract: A principal animal paradigm employed in Anorexia Nervosa (AN) study is the activity-based anorexia (ABA) model. The model's efficacy in recapitulating the core features of AN in humans allows for the study of the parameters involved in the disorder. The current study examined the susceptibility to the ABA protocol in the presence of a significant stressor (maternal separation) in male and female Sprague Dawley rats. More importantly, we analysed the sex-differences on activity levels during different periods of the ABA protocol to determine the period(s) influencing the most pathological weight loss. Both components of the ABA protocol contributed to the subjects' bodyweight loss. Stress in the first two weeks of development conferred a protective effect in males. Time spent and activity levels on the running wheel were higher in females compared to males. Hyperactivity in ABA subjects was observed during the food-anticipatory activity (FAA) and postprandial activity in males and during the FAA and nocturnal activity periods in females. This study aids in understanding the effect of intensity of activity during specific periods on the pathological weight loss in ABA rats. These observations are informative for therapies aimed at ameliorating body mass index in AN patients. Highlights: Implementing the ABA protocol revealed a higher female to male vulnerability. MS + ABA resulted in a decreased susceptibility to the ABA protocol especially in males. Higher food anticipatory and nocturnal activity impacted weight loss in ABA females. Higher food anticipatory and postprandial activity impacted weight loss in ABA males.